SOCIOLINGUISTIC ANALYSIS OF THE SONGS BY THE ROCK GROUP TRÉMOLO - Ochoa, Jessica (2011)
This work deals with a sociolinguistic study based on the analysis of the Songbookof the band Trémolo. For this purpose we consider the theoretical framework offunctional linguistic varieties concerning the construction of a certain contextboundlinguistic register.